Sistem Informasi Layanan Jasa CCTV dan AC di CV Adhi Nawa Jaya Menggunakan Metode Waterfall - Umrotin Khasanah; Arief Saputro; Syahri Mu’min (Institut Teknologi Adhi Tama Surabaya, 2022)
CV Adhi Nawa Jaya is a company engaged in the service sector. In the current era of increasingly sophisticated information technology development, there are still service provider companies that do marketing using print media such as banners and banners. For that, we need a media in the form of a website as a marketing system that is more effective and efficient. The research method used is data collection techniques, observation, interviews, literature studies, while the system development model used is the waterfall method which consists of four stages, namely the analysis, design, testing and implementation stages. As a result, the Service Ordering Information System on CV Adhi Nawa Jaya, can be used as a source of marketing information for service companies, and can expand marketing reach.